The impact of regulation on the asset investment of defined benefit pension funds - Franzen, D; Dorothee Franzen (2013)
Pension funds are important institutions providing retirement income in our ageing societies and influential investors on international capital markets. Investment is a core function at pension funds; the investment return is an important tool in providing adequate pension benefits at sustainable costs. Risk taking is a necessary ingredient in pension provision, which is shaped through the intersecting forces of theory, market and regulation. This century's financial crises deeply unsettled the pension fund universe. When the benign environment of the 1990s ended, DB pension funds found themselves at the intersection of financial turmoil and tightening regulatory and accounting trends, which marked a caesura to investment and risk management strategies: Pension funds have started to de-risk. This thesis investigates the impact of regulation on the asset investment of occupational defined benefit (DB) pension funds in selected OECD countries in an effort to understand both the reasons for changing patterns of investment and the reasons for persisting differences. I suggest that the traditional consensus of pension risk taking and sharing is broken. The tightening web of regulatory and accounting rules has impeded pension funds risk taking capacity. A re-design of pension risk sharing is a necessary ingredient for shaping the pension fund system of the 21st century. Furthermore, pension funds regulation should be better aligned with social policy goals to cope with the transformation of pension systems initiated by demographic, economic and societal change.